Exploring Empathy and Satisfaction Dynamics in Veterinary Medical Interviews among Companion Animal Veterinarians and Pet Owners in Kerala, India - , Ryan Leander D’souza; , P. Reeja George; , R. Senthilkumar; , R.S. Jiji; , V.L. Gleeja; , Ajith Y. (Archives of Current Research International, 2025)
Veterinary medical interviews are pivotal to companion animal care, directly influencing clinical outcomes and client satisfaction. This study explores the satisfaction levels of companion animal veterinarians and pet owners with these interviews and highlights a disturbing trend with regard to the role of veterinarian empathy and its effect on veterinarian satisfaction in this process. The study was conducted in the state of Kerala in India among 60 randomly selected companion animal veterinarians and 60 pet owners selected at random from four districts with the highest canine populations in the area of study. Results indicated that most veterinarians reported low (46.70 per cent) to medium (48.30 per cent) satisfaction despite medium (35.00 per cent) to high (63.30 per cent) self-rated empathy levels. The results of this study indicated that most of the pet owners reported a medium (31.70 per cent) to high (63.30 per cent) of satisfaction with the interviews. A significant positive association was found between veterinarian satisfaction and empathy; however, veterinarian satisfaction was negatively associated with owners’ perception of communication behaviours. The lack of association between veterinarian empathy and owner satisfaction highlights the complex interplay between empathy, professional satisfaction, and client perceptions. Findings suggest that empathic over-arousal may contribute to reduced veterinarian well-being, potentially reflecting compassion fatigue. This study underscores the need for further exploration of empathy’s dual role as a professional asset and risk factor in veterinary medicine to enhance the communication process and client satisfaction with the veterinary medical interval.